Trig

posted by .

prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)

  • Trig -

    cscx-secx/cscx+secx
    = cos/cos * cscx-secx/cscx+secx
    = (cos*csc - 1)/(cos*csc + 1)
    = (cot-1)/(cot+1)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. trig

    express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
  2. Trig

    Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (x=theta BTW)
  3. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
  4. Pre-Calculus

    Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
  5. Precalculus

    Complete the following identity secx-1/secx=?
  6. Pre Calculus

    (secx)/(tanx)+(cscx)/(cotx)=secx+cscx Please help me verify this trigonometric identity.
  7. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  8. Pre Calculus

    (cotx)(cscx)+secx=(csc^2x)(secx) Please help to verify this trigonometric identity.
  9. trig proofs

    cotx+tanx=secx+cscx
  10. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions